Expert opinion on the management of hepatitis C infection in Kuwait - Saad MF (Dove Medical Press, 2018)
Motaz Fathy Saad,1 Saleh Alenezi,2 Haifaa Asker3 On behalf of the Kuwait Hepatology Club 1Haya Al-Habib Gastroenterology and Hepatology Center, Mubarak Alkabir Hospital, Hawaly, Kuwait; 2Unit of Gastroenterology and Hepatology, Department of Medicine, Farwaniya Hospital, Kuwait City, Kuwait; 3Thunayan Al-Ghanim Gastroenterology and Hepatology Center, Al-Amiri Hospital, Kuwait City, Kuwait Abstract: Chronic hepatitis C virus (HCV) infection is a leading cause of death, especially in immunocompromised patients. The lack of clear prevalence data in the Middle East makes it difficult to estimate the true morbidity and mortality burden of HCV. In Kuwait, estimating the burden of disease is complicated by the constant flow of expatriates, many of whom are from HCV-endemic areas. The development of new and revolutionary treatments for HCV necessitates the standardization of clinical practice across all healthcare institutions. While international guidelines from the American Association for the Study of Liver Diseases (AASLD) and European Association for the Study of the Liver (EASL) do address this evolving treatment landscape, the cost-driven treatment prioritization of patients by these guidelines and unique HCV genotype presentation in the Kuwaiti population prompted the development of a more tailored approach. The predominant HCV genotypes prevalent in Kuwait are genotypes 4 and 1. The Kuwait Hepatology Club (KHC), comprising hepatologists across all major institutions in Kuwait, conducted several consensus meetings to develop the scoring criteria, evaluate all current evidence, and propose screening, diagnosis, and treatment suggestions for the management of HCV in this population. While these treatment suggestions were largely consistent with the 2016 AASLD and 2015 EASL guidelines, they also addressed gaps in the unmet needs of the Kuwaiti population with HCV. Keywords: hepatitis C, diagnosis, treatment, management, Kuwait